Biocompatible dual network bovine serum albumin-loaded hydrogel-accelerates wound healing. (17th February 2023) - Liu, Dongmei; Zhao, Susu; Jiang, Yujie; Gao, Chuanhui; Wu, Yumin; Liu, Yuetao
Graphical abstract: Highlights: BSA-PCDN hydrogels were prepared by copolymerizing BSA with polymerizable monomers by utilizing the binding ability of albumin to drugs. BSA-PCDN hydrogel improved the mechanical strength of natural protein hydrogel with a maximum stress of 1.17 MPa. BSA-PCDN hydrogel has good biocompatibility and wound closure performance in mouse skin incision model. Abstract: Hydrogels with good biocompatibility and the ability to maintain a moist environment at the wound site, as well as good drug-carrying capacity and slow-release properties, can be used as medical materials for wound dressings. Albumin is the primary plasma protein and the physiological carrier of a wide range of compounds, including drugs. To exploit the binding ability of albumin to drugs, we prepared bovine serum albumin-P (Acrylic acid- co -Acrylamide- co - N -Vinylpyrrolidone- co -Hydroxyethyl methacrylate- co -γ-(methacryloyloxy) propyltrimethoxysilane) double network hydrogels by copolymerizing BSA with various easy-to-polymerize monomers. The synthesized double network hydrogels can substantially improve the mechanical strength of natural protein-based hydrogels with a maximum stress of 1.17 MPa. Due to the good biocompatibility and stable drug release properties of BSA, in vitro evaluation in a mouse skin incision model showed that the hydrogels had a high wound closure effect, providing a feasible strategy for rapid skin wound healing.